Facile synthesis of solution-processed MoS2 nanosheets and their application in high-performance ultraviolet organic light-emitting diodes. Issue 4 (7th January 2019) - Zhang, Xiaowen; Li, Wanshu; Ling, Zhitian; Zhang, Yan; Xu, Jiwen; Wang, Hua; Chen, Guohua; Wei, Bin
Abstract : High-performance ultraviolet organic light-emitting diodes are assembled using liquid-phase exfoliated MoS2 and its composites, MoS2 –UVO and MoS2 +PEDOT:PSS. Abstract : Solution-processed aqueous molybdenum disulfide (MoS2 ) nanosheets with good dispersity and air stability were synthesized in a facile manner through liquid-phase exfoliation. MoS2 and corresponding composites of ultraviolet/ozone-treated MoS2 (MoS2 –UVO) and MoS2 -doped poly(3, 4-ethylenedioxythiophene):poly(styrene-sulfonate) (MoS2 +PEDOT:PSS) were characterized using atomic force microscopy and X-ray/ultraviolet photoelectron spectroscopy, confirming superior film morphology and exceptional electronic properties. High efficiencies of 8.1 cd A −1 and 5.7 lm W −1 were demonstrated in visible organic light-emitting diode (OLED) with tris(8-hydroxy-quinolinato)aluminum as the emissive layer and MoS2 +PEDOT:PSS as the hole-injection layer. Using 3-(4-biphenyl)-4-phenyl-5- tert -butylphenyl-1, 2, 4-triazole as emitter and MoS2 +PEDOT:PSS for hole-injection tuning, the fabricated ultraviolet OLED produced attractive short-wavelength electroluminescence of 376 nm with a full-width at half-maximum of 37 nm and improved stability. The radiance and external quantum efficiency reached 11.9 mW cm −2 and 4.14%, respectively. Current–voltage characteristics and impedance spectroscopy confirmed that the hole-injection capacity increased in the order MoS2 < MoS2 –UVO < MoS2 +PEDOT:PSS. The extremely promoted hole injection of MoS2 +PEDOT:PSS accounted for its outstanding device performance. Our results provide a novel approach for advancing MoS2 applications with solution processing and scalable manufacturing.